2018 IEEE Games, Entertainment, Media Conference (GEM) 2018
DOI: 10.1109/gem.2018.8516539
|View full text |Cite
|
Sign up to set email alerts
|

DOOM Level Generation Using Generative Adversarial Networks

Abstract: We applied Generative Adversarial Networks (GANs) to learn a model of DOOM levels from human-designed content. Initially, we analyzed the levels and extracted several topological features. Then, for each level, we extracted a set of images identifying the occupied area, the height map, the walls, and the position of game objects. We trained two GANs: one using plain level images, one using both the images and some of the features extracted during the preliminary analysis. We used the two networks to generate n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…We predict that in the near future, generative modelling techniques from machine learning, such as Generative and Adversarial Networks (GANs) [24], will allow users to personalise their avatars to an unprecedented level or allow the creation of an unlimited variety of realistic textures and assets in games. This idea of Procedural Content Generation via Machine Learning (PCGML) [81], is a new emerging research area that has already led to promising results in generating levels for games such as Doom [23] or Super Mario [87].…”
Section: Journals Conferences and Competitionsmentioning
confidence: 99%
“…We predict that in the near future, generative modelling techniques from machine learning, such as Generative and Adversarial Networks (GANs) [24], will allow users to personalise their avatars to an unprecedented level or allow the creation of an unlimited variety of realistic textures and assets in games. This idea of Procedural Content Generation via Machine Learning (PCGML) [81], is a new emerging research area that has already led to promising results in generating levels for games such as Doom [23] or Super Mario [87].…”
Section: Journals Conferences and Competitionsmentioning
confidence: 99%
“…They trained two GANs: one using plain level images, one using both the images and some of the features. Their results showed that GANs could generate structure of DOOM levels in first person shooter games [34].…”
Section: Related Workmentioning
confidence: 99%
“…With the recent advancement of deep learning technology, various deep learning technologies are influencing game development. The GAN algorithm adopted in level generation has been applied on a pilot basis to a large number of dungeons and level generation [1][2][3]. Convolution neural network (CNN) or parameter-based reinforcement learning algorithms applied to nonplayable characters (NPC) are used to develop NPC that can learn user behavior patterns [4][5][6].…”
Section: Introductionmentioning
confidence: 99%